Dayside Magnetospheric and Ionospheric Responses to a Foreshock Transient on 25 June 2008: 1. FLR Observed by Satellite and Ground‐Based Magnetometers. Issue 8 (15th August 2018) - Shen, Xiao‐Chen; Shi, Quanqi; Wang, Boyi; Zhang, Hui; Hudson, Mary K.; Nishimura, Yukitoshi; Hartinger, Michael D.; Tian, Anmin; Zong, Qiu‐Gang; Rae, I. J.; Degeling, Alexander W.
Abstract: As one type of driver of magnetospheric Alfvén waves, foreshock transients have received less attention than, for example, the Kelvin‐Helmholtz instability, discrete and broadband frequency solar wind dynamic pressure oscillations, and interplanetary shocks. Previous works show that foreshock transients can induce both Alfvén mode and compressional mode Pc 3–5 ULF waves inside the magnetosphere. However, to our knowledge, none of these reported Pc 3–5 waves, induced by foreshock transients, are proved to be localized in the magnetosphere. In this paper, using in situ and ground‐based observations, we report the generation of localized magnetospheric compressional waves and field line resonances (FLRs) by a foreshock transient. Both the foreshock transient and Pc 5 ULF waves were found on the duskside; while on the morning side of the magnetosphere, no clear wave signatures were captured. Our results demonstrate that in addition to the global effects of foreshock transients on the magnetosphere reported earlier, foreshock transients can also generate localized magnetospheric responses in the Pc 5 range with clear dawn‐dusk asymmetry. A suite of eight dayside spacecraft plus ground magnetometer measurements make possible the determination of the foreshock transient driver and dawn‐dusk asymmetry of the magnetospheric response not previously reported with such a complete data set. Key Points: Both Pc 5 compressional and Alfvén waves are found to be generated by a foreshock transient Magnetospheric responses in the Pc 5 range are localized with clear dawn‐dusk asymmetry The dawn‐dusk asymmetry of wave power is consistent with the MLT location of the foreshock transient